2020
DOI: 10.1177/2042098620935721
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge assessment of snake antivenom among healthcare practitioners involving educational intervention in northern Nigeria: a study protocol

Abstract: Introduction Snakebite envenoming (SBE) is an important occupational and public health hazard especially in sub-Saharan Africa. For optimum management of SBE, adequate knowledge of Snake antivenom (SAV) is very critical among the healthcare practioners in this region. Information related to the knowledge of SAV use in the management of SBE, as well as SAV logistics is scarce among the Health Care Professionals (HCPs) in Nigeria, particularly in the northern region. We therefore aimed to develop, validate and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Furthermore, knowledge regarding prescription and antivenom administration was relatively poor among HCWs, with less understanding among "clinicians" than nurses. Similar findings have been reported in Ghana, where HCWs overestimated their knowledge about snakebite management [ 24 ], and in Nigeria, where the knowledge about SAV among HCWs was grossly inadequate [ 28 ]. Patterns of lack of knowledge among HCWs on snakebite and SAV prescription and administration have also been reported in Brazil, Palestine, Kenya, Uganda, and Zambia [ 16 , 18 , 33 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, knowledge regarding prescription and antivenom administration was relatively poor among HCWs, with less understanding among "clinicians" than nurses. Similar findings have been reported in Ghana, where HCWs overestimated their knowledge about snakebite management [ 24 ], and in Nigeria, where the knowledge about SAV among HCWs was grossly inadequate [ 28 ]. Patterns of lack of knowledge among HCWs on snakebite and SAV prescription and administration have also been reported in Brazil, Palestine, Kenya, Uganda, and Zambia [ 16 , 18 , 33 ].…”
Section: Discussionsupporting
confidence: 82%
“…Health care workers’ (HCWs’) knowledge and compliance with standardized protocols for diagnosis and treatment remain crucial for managing snakebites [ 24 27 ]. Studies performed in Cameroon, Nigeria, and Lao PDR have shown that the level of knowledge among HCWs on snakebites remains poor [ 15 , 28 , 29 ]. In Bhutan, a study found that only 23% of HCWs had an adequate understanding of the management of snakebite envenoming, while in Ghana, a study showed a slightly higher level of knowledge at 48.2% [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“… 25 27 Both the AKAT and the study protocol have been published elsewhere by the same authors. 22 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27] Both the AKAT and the study protocol have been published elsewhere by the same authors. 22,24 The ASV tool consists of a total of 28 items covering knowledge (19 items), availability, cost, and logistics (9 items) of ASV in northern Nigeria. The availability, cost, and logistics were presented as frequencies and percentages.…”
Section: Asv Assessment Toolmentioning
confidence: 99%
“…The clinical management of SBE entails hospitalization, administration of effective antivenoms, and provision of supportive care by Health Care Workers (HCWs). Studies have shown low levels of education among HCWs in developing countries ( Michael et al, 2018 ; Bala et al, 2020a , Bala et al, 2020b ), and it has been established in northern Ghana that the outcome of care, including deaths from SBE, depends partly on the knowledge of HCWs and their compliance to standardized protocols, and on the availability of effective antivenom. There, the impact of training of HCWs was shown to reduce mortality from SBE ( Visser et al, 2004 ).…”
Section: Improving Education and Trainingmentioning
confidence: 99%